Earnings persistence of European football clubs under UEFA's FFP - Panagiotis E. Dimitropoulos; Konstantinos Koronios (International Journal of Financial Studies, 2018)
The goal of this study was to examine the predictability and persistence of earnings of the European football clubs and whether the new Union of European Football Associations (UEFA) Financial Fair Play (FFP) licensing regulation has forced clubs to produce a more predictable earnings stream. We utilized a sample of 109 European top-tier clubs over the period 2008-2016, summing up to 844 firm-year observations. Empirical evidence indicated that the cash flow component of earnings is more relevant in predicting one-year ahead earnings than accruals. This positive impact of cash flows for predicting earnings is more significant after the FFP regulation since earnings predictability has increased during that period. Moreover, the abovementioned finding is more significant for the smaller league clubs rather than the Big-5 league clubs. This finding is attributed to the fact that smaller league clubs are more in need of UEFA prize money relative to Big-5 league clubs, thus they are more incentivized to produce a more predictable earnings stream.
Keywords: M41; G32; G34; 330; earnings persistence; accruals; earnings predictability; European football clubs; financial fair play